Empowering MSMEs with Data-Driven Insights: Mobile Sales Dashboard Application for MSMEs - Zalina Fatima Azzahra; Riska Yanu Fa'rifah; Syfa Nur Lathifah (Departemen Sistem Informasi, Fakultas Teknologi Informasi, Universitas Andalas, 2025)
Micro, Small, and Medium Enterprises (MSMEs) in Indonesia have made a large contribution to GDP and the workforce but still face challenges in managing sales data and making data-driven decisions. Manual recording often causes operational inefficiencies, recording errors, and delays in business analysis. Based on the previous problem, this study develops a mobile-based sales dashboard application to help MSMEs analyse data in real-time and improve business strategies. The methodology used is Design Science Research (DSR) with a Rapid Application Development (RAD) approach for rapid and iterative development. This application was developed using Java and Firebase and provides sales summary features, best-selling cashiers, best-selling products, and less popular products, with time filters and graphical data visualization. Testing using Black Box Testing shows that all features run well, while the results of the User Acceptance Test (UAT) show that 90.625% of users feel that this application is easy to use and suits their needs. These results indicate that the application can improve operational efficiency and business transparency and support data-driven decision-making for MSMEs.